Nonsymmetric problem of divisors in an arithmetic progression - Koverdyuk І. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate the distribution of values of a nonsymmetric divisor functiond(a,b; n) in an arithmetic progression with increasing difference.